HIV infection during limited versus combined HIV prevention programs for IDUs in New York City: The importance of transmission behaviors - Des Jarlais, Don C.; Arasteh, Kamyar; McKnight, Courtney; Hagan, Holly; Perlman, David C.; Torian, Lucia V.; Beatice, Sara; Semaan, Salaam; Friedman, Samuel R. (Drug and alcohol dependence, 2010)
As no single HIV prevention program has eliminated HIV transmission, there is growing interest in the effectiveness of “combined” prevention programming. To compare HIV infection among persons injecting in the initial programs environment (IPE) in New York City (self-initiated risk reduction, methadone, education/outreach, and HIV testing) to HIV infection among persons injecting in a combined programs environment (CPE) (above programs plus large-scale syringe exchange). To identify potential behavioral mechanisms through which combined programs are effective. Subjects were recruited from the Beth Israel drug detoxification program. A risk behavior questionnaire was administered and HIV testing conducted. Subjects who injected only between 1984 and 1994 (IPE) were compared to subjects who injected only between 1995 and 2008 (CPE). 261 IPE subjects and 1153 CPE subjects were recruited. HIV infection was significantly lower among the CPE subjects compared to IPE subjects: prevalence 6% versus 21%, estimated incidence 0.3/100 person-years versus 4/100 person-years (both p < 0.001). The percentage of subjects at risk of acquiring HIV through receptive syringe sharing was similar across CPE and IPE subjects (30% versus 33%). The percentage of subjects at risk of transmitting HIV through injection-related behaviors (who were both HIV seropositive and reported passing on used needles/syringes), was much lower among the CPE subjects than among the IPE subjects (1% versus 10%, p < 0.001). Combined prevention programs can greatly reduce HIV transmission. Reducing distributive sharing by HIV seropositive injecting drug users (IDUs) may be a critical component in reducing HIV transmission in high seroprevalence settings.